A review of Scope and Limitations of Organizational Behavior - Yamini (Innovative Research Thoughts, 2018)
The success of any given organization is inextricably linked to the caliber of its management, which in turn is predicated on the management team's human abilities and its capacity to anticipate and meet the wants and requirements of its constituents. Because organisations do not exhibit any kind of behavior on their own, the term "organizational behavior" refers instead to the actions of those working inside them. It is generally acknowledged that the growth of an organization is directly tied to the growth of its employees. The study of organizational behavior examines how factors such as individual traits, group dynamics, and organizational structure influence employee actions in the workplace.